Vertex Extradural Hematoma: A Diagnostic Dilemma - Kumar, Jayendra (Asian J Neurosurg, 2017)
Extradural hematomas (EDHs) of vertex are rarely seen and form a small percentage of all EDH. Usual cause of an EDH located at the vertex is tearing of the superior sagittal sinus. A 35-year-old male patient was admitted to our department, with history of fall and lucid interval. Imaging studies showed contusion in the right frontal region with midline shift and bilateral EDH located at vertex which was misinterpreted as artifact or subdural hematoma. We present this rare case and briefly review the literature regarding its etiopathology and associated clinico-radiological findings. The principles of management of this rare entity are also discussed.